Characterization an wooden Pietà sculpture from the XVIII century using XRF and microct techniques. (January 2023) - Sanches, Francis Anna C.R.A.; Nardes, Raysa C.; Santos, Ramon S.; Gama Filho, Hamilton S.; Machado, Alessandra S.; Leitão, Roberta G.; Leitão, Catarine C.G.; Calgam, Teresa E.; Bueno, Regina; Assis, Joaquim T.; Oliveira, Davi F.; Lopes, Ricardo T.; et al.
Abstract: In this work the pigments, ground layer and the structure of a polychrome wooden Pietà sculpture from the 18th century was characterized using X-ray fluorescence and computed microtomography (microCT) techniques. It was possible to detect the elements: Ca, Ti, Fe, Cu, Zn, Ba, Au, Hg and Pb. It was possible to characterize the pigments Azurite, Prussian Blue, Green Earth, Vermilion, Lead white, Zinc white, and Gold foils. In the regions where there were restorations, it was possible to identify the presence of the lithopone pigment, indicating that these processes occurred from the 19th century. The microCT showed that the statue is a carved wood sculpture with a painting layer with high density pigments. Two different blocks of wood were identified joined together with a wooden pin. The statue was attached to its wooden base with different types of nails, showing that this step took place in a period of time later than the statue manufacturing. Details of the attaching of the eyes and damages due to insect galleries could be also found in this statue. Highlights: Cultural heritage objects analysis using X-ray fluorescence (XRF) and microCT) techniques. Analysis of the internal structure of a wood sculpture using the microCT technique. The microCT technique identified a base later added to the sculpture. The XRF technique characterized of the pigments and the preparation layer. The XRF technique allowed to characterize restoration areas.